UD Packs Dodol Processing in Wonosari, Bengkalis District, Bengkalis Regency - Halimatiara Halimatiara; Riska Ardila Hasanah; Dea Putri Ananda; Rizki Maulana (Jurnal Ekonomi, Manajemen, Bisnis dan Akuntansi Review, 2023)
The purpose of this study is to determine the marketing strategy for UD Kemas home industry dodol, which is situated in Bengkalis District, Bengkalis Regency. Additionally, the study will investigate the opportunities, threats, strengths, and weaknesses that are related with the marketing of UD Kemas dodol. The method of data analysis that is utilised is a descriptive analysis that draws upon the strengths, weaknesses, opportunities, and threats analytical approach. First, the internal factor evaluations (IFE) and the external factor evaluations (EFE) are determined using this approach. Next, the right strategy is determined by employing the IE matrix and the SWOT matrix. Finally, the process concludes with the determination of the appropriate strategy. Taking into consideration the results of this research, it is possible to draw the conclusion that the execution of a progressive strategy at dodol UD Kemas, which is situated in the Bengkalis District of the Bengkalis Regency, is indicative of a healthy business that has the potential to be developed. Using the SO strategy that was generated from the findings of the questionnaire, it is possible to grow demand for UD Kemas dodol even further by ensuring that product excellence is maintained and maintained. Strategic locations can be utilized to make the product sales process easier.